Obturator hernia: A rare condition with common surgical symptoms - Amran, Fitreena Anis; Che Alhadi, Shahidah; Md Hashim, Mohd Nizam; Wan Zain, Wan Zainira; Wong, Michael P.K. (AMDI Press, 2018)
Hernia is a common surgical problem. However, worldwide incidence of obturator hernia is <1% of all hernia cases, occurring more commonly in thin, elderly and multiparous female. An 82 years old lady presented with bowel obstruction sign and symptoms for 4 days duration. Imaging study, computed tomography with enhanced contrast (CECT) of abdomen and pelvis showed small bowel obstruction secondary to left obturator hernia. Emergency abdominal exploration with left transverse transperitoneal approach was performed. Intraoperatively, anti mesenteric part of ileal wall was incarcerated through the left obturator foramen causing small bowel obstruction and it was resected with end to end anastomosis. She recovered well and was discharged on postoperative day 7. The signs and symptoms of obturator hernia are non-specific. Most cases are presented with symptoms of intestinal obstruction, resulting in diagnostic difficulty for this rare condition. Delay in diagnosis and surgical intervention contribute to poorer outcomes.